O processo de otimização da remoção de fósforo e nitrogênio no Central Clark County Water Reclamation District plant em Las Vegas: Nevada: EUA - Boeing, Alisson Luiz (2014)
The excessive accumulation of nutrients in water such as phosphorus and nitrogen can cause serious ecological problems and public health. The Clark County Water Reclamation District operates 7 treatment facilities. The Facilities treats millions of liters of wastewater per day utilizing physical, chemical and biological processes. The present work aims to explore different operational schemes to increase denitrification at the Flamingo Treatment Plant while at the same time maintain phosphorus removal. The theoretical calculation of phosphorus and nitrogen removal using computer modeling was carried out and compared with the results obtained in the treatment plant, assuming an A2O system. The results were evaluated by performing the average, standard deviation, maximum and minimum of orthophosphate, ammonia, nitrate and nitrite. The results indicated that phosphorus and nitrogen removal can be reached in the A2O configuration. Through the collections and analyses, it was observed that the process had a good removal of phosphorus and nitrate, but high concentrations of ammonia occurred during the tests. Hence, the parameters meet the effluent requirements in the State of Nevada, but a greater solids retention time should be tested to achieve greater process efficiency.